2015
DOI: 10.1021/es504826d
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term (∼57 ka) Controls on Mercury Accumulation in the Souther Hemisphere Reconstructed Using a Peat Record from Pinheiro Mire (Minas Gerais, Brazil)

Abstract: Natural archives have been used to reconstruct mercury atmospheric deposition at different spatial and temporal scales during the Holocene in the Northern Hemisphere. In this study, we present the results from a Brazilian mountain mire (Pinheiro mire, Minas Gerais, SE Brazil), extending back to ∼57 ka. The core was analyzed for mercury concentration, organic matter content, organic carbon isotopic composition, and tracers of mineral matter flux. Principal components analysis followed by principal components re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 79 publications
1
23
0
Order By: Relevance
“…The main advantage of using component scores rather than the original geochemical data in the regression analysis is that the rotated components represent new synthetic orthogonal variables, and the effects of these components within the regression analysis are additive. The record of the regression weights of the components with depth/time was used to evaluate the chronological variations of the controls on the Hg record [51]. All statistical calculations were performed within the statistic environment of R-version 3.3.3 [52].…”
Section: Statistical Treatmentmentioning
confidence: 99%
“…The main advantage of using component scores rather than the original geochemical data in the regression analysis is that the rotated components represent new synthetic orthogonal variables, and the effects of these components within the regression analysis are additive. The record of the regression weights of the components with depth/time was used to evaluate the chronological variations of the controls on the Hg record [51]. All statistical calculations were performed within the statistic environment of R-version 3.3.3 [52].…”
Section: Statistical Treatmentmentioning
confidence: 99%
“…The main advantage of using component scores rather than the original geochemical data in the regression analysis is that the rotated components represent new synthetic orthogonal variables, and the effects of these components within the regression analysis are additive. The record of the regression weights of the components with depth/time was used to evaluate the chronological variations of the controls on the Hg record [50]. All statistical calculations were performed within the statistic environment of R -version 3.3.3 [51].…”
Section: Statistical Treatmentmentioning
confidence: 99%
“…In this work, we found that three of the four main processes controlling Hg concentration depended on climate: wet and dry Hg deposition (rainfall and dustfall, respectively), as well as local catchment soil erosion owing to precipitation events [29]. The effect of long-term peat decomposition, the only autogenic process identified, was confined to the Holocene section of the peat [29].…”
Section: Introductionmentioning
confidence: 81%
“…In a recent work, we studied Hg accumulation in Pinheiros (18 • S, 43 • W) [29], a Pleistocene age (last~57 ka) tropical mire located in a valley in Serra do Espinhaço Meridional (state of Minas Gerais, Brazil). In this work, we found that three of the four main processes controlling Hg concentration depended on climate: wet and dry Hg deposition (rainfall and dustfall, respectively), as well as local catchment soil erosion owing to precipitation events [29]. The effect of long-term peat decomposition, the only autogenic process identified, was confined to the Holocene section of the peat [29].…”
Section: Introductionmentioning
confidence: 99%